Pengaruh Anggaran Berbasis Kinerja Terhadap Peningkatan Kinerja Aparatur Pemerintah Daerah (Studi Pada Dinas Sosial Provinsi Kalimantan Timur) - Fratiwi, U'ah Ganda; Utary, Anis Rachma; Irwansyah, Irwansyah (Fakultas Ekonomi dan Bisnis Universitas Mulawarman, 2018)
U'ah Ganda Fratiwi, budget influence based on performance toward increasing local goverment agencies performance (study on social department of East Kalimantan Province). Supervised by Mrs. Anis Rachma Utary and Mr. Irwansyah. The purpose of this research is to know budget influence based on performance toward increasing local goverment agencies performance on social department of East Kalimantan Province.This research is quantitative research. The data was taken is primer data used likert scale. Respondences in this research are civil goverment in the part of financial management. Independent variable in this research is budget based on performance (x) and dependent variable is local government agencies performance (y). The analysis instrument in this research was used partial least square as analysis instrument. Based on result of the research can concluded that budget variable based on performance have positive influence and significance toward increasing local goverment those are 56,7% and the balance are 43,3% was influence by another variable thet is not exist in this research.